Pemberdayaan Masyarakat Melalui Pelatihan Pengolahan Sabut Kelapa Menjadi Pupuk Organik Cair di Desa Semambu Kuning Kabupaten Indragiri Hilir - Sulistyani, Andri; Azzahra, Karenina; Hafizah, Mauke Puan; Yunita, Norma; Deani, Silvia; H, Hikmal Syahbani; Kasyfurrahman, Fachri Asyura; Sabilla, Annisa (Unri Conference Series: Community Engagement, 2024)
Waste coconut fiber can be converted into a liquid organic fertilizer that is extremely beneficial to plants. The composition of organic fertilizer made from coconut fiber can aid in providing the nutrients that plants require. The purpose of community service projects is to observe how the growth of vegetable and fruit plants is affected by the availability of liquid organic fertilizer (POC) made from coconut fiber, to reduce the amount of waste generated by coconut fiber, and to teach the community how to turn waste coconut fiber into marketable products that will boost the output of UMKM. Indragiri Hilir Regency's Semambu Kuning Village is where this community service was completed. The techniques employed were counseling and demonstrations, wherein KKN students were given direct instruction on how to make POC based on coconut fiber and were also given theories about liquid organic fertilizers. The community service outcomes demonstrated two things: 1) The local village community expressed interest in converting waste coconut fiber into liquid organic fertilizer with marketable value for resale; and 2) Plant growth and development are positively impacted by the availability of this product. The conclusion of this activity is that the POC demonstration provides new ideas to the village community in utilizing coconut fiber waste that has the potential to be traded.